2020
DOI: 10.1111/nep.13723
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of Immunoglobulin A nephropathy with crescents in a multi‐ethnic Southeast Asian cohort

Abstract: AimClinical presentation and course of Immunoglobulin A nephropathy vary by ethnicity and geography and significance of extracapillary proliferation or crescents (IgAN‐C) in Southeast Asia is not well described. We aimed to describe the clinical course of IgAN‐C in Singapore.MethodsRetrospective cohort study of adult biopsy‐proven IgAN diagnosed between February 2011 and October 2016 in 2 hospital‐based nephrology units. Outcome was chronic kidney disease (CKD) progression, defined as reduction in eGFR ≥50% or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Primary IgA nephropathy is more common, accounting for about 36.7% to 58.2% of primary glomerular diseases diagnosed by renal pathology in China, and its incidence has been gradually increasing in recent years [1,2]. It can be seen at any age, and patients aged 16-35 years account for about 80% of the total number of patients with the disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Primary IgA nephropathy is more common, accounting for about 36.7% to 58.2% of primary glomerular diseases diagnosed by renal pathology in China, and its incidence has been gradually increasing in recent years [1,2]. It can be seen at any age, and patients aged 16-35 years account for about 80% of the total number of patients with the disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, crescents in IgA nephropathy were not found to be statistically associated with increased probability of progression to end-stage renal disease. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Kidney histology in the form of the Oxford MEST-C score can prognosticate kidney failure in IgAN [ 3 ], but its role in guiding immunosuppression remains uncertain [ 4 ]. We previously reported that among our multi-ethnic Southeast Asians with biopsy-proven IgAN with crescents, immunosuppressive therapy tended to lower the risk of rapid kidney disease progression [50% reduction in estimated glomerular filtration rate (eGFR) or kidney failure at 12 months] and significantly reduced kidney failure [ 5 ]. While other studies have also explored the impact of immunosuppressants on kidney outcomes according to the presence and extent of crescents [ 6 , 7 ], Itami et al .…”
mentioning
confidence: 99%
“…In our dataset of 66 IgAN with complete clinical and histological data [ 5 ], SRS were low, medium and high in 4 (6%), 33 (50%) and 29 patients (44%), respectively. The median age was 46.8 (interquartile range 36.6, 58.5) years and systolic and diastolic blood pressures were 128 (119, 140) and 71 (70, 80) mmHg, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation